1992
DOI: 10.1111/j.1464-410x.1992.tb15535.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of a Single Testis: Always, Sometimes or Never

Abstract: If it is necessary to perform an orchiectomy for an intravaginal testicular torsion it is the usual practice of surgeons to fix the contralateral testis. When faced with a child with only one testis for another reason it is our practice to fix this single testis to eliminate the small but disastrous risk of a torsion. We were interested to see whether this practice was usual and therefore sent out a questionnaire to the 67 consultant paediatric surgeons and urologists in Great Britain. Sixty-six surgeons repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…Other factors predicting spontaneous descent are low birth weight, large scrotal size, bilateral cryptorchidism and lower testicular location at presentation 8. The first case of testicular torsion in a UDT was reported in 1840 9 10. UDT is prone to torsion due to various reasons such as the lack of anatomic fixation of the gonads in the scrotum and the possibility of spasmodic contractions of the cremaster muscle 10 11.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors predicting spontaneous descent are low birth weight, large scrotal size, bilateral cryptorchidism and lower testicular location at presentation 8. The first case of testicular torsion in a UDT was reported in 1840 9 10. UDT is prone to torsion due to various reasons such as the lack of anatomic fixation of the gonads in the scrotum and the possibility of spasmodic contractions of the cremaster muscle 10 11.…”
Section: Discussionmentioning
confidence: 99%
“…Following these concepts and although the possibility of contralateral testicular torsion is extremely low but certain, there is consensus in exploring the contralateral side [1,4,5,9,10,33,34] in the same operation or soon after that, depending on the local conditions and the clinical status of the patient.…”
Section: If Torsion Occurs In the Prenatal Period Near Birthmentioning
confidence: 99%
“…Bellinger found abnormal testicular fixation in 5/6 contralateral testes explored following the diagnosis of monorchia [5]. Harris et al found 13 cases of BCD in 15 patients [6], and hence concluded, as did Mishriki et al, that the remaining testis was at risk in congenital monorchia, and should be fixed [1]. However, in the study by Al-Zahem and Shun only 3/31 patients (10%) were found to have BCD [7].…”
Section: Discussionmentioning
confidence: 76%
“…In 1992, a team from Bristol sent a similar questionnaire to 67 paediatric surgeons in the UK [1]. The results showed that there was no unanimity regarding the question of fixation of the single testis except following intravaginal postnatal torsion.…”
Section: Discussionmentioning
confidence: 96%